Korelasi Pendidikan Agama Kristen dengan Perkembangan Karakter Siswa - Thomson Siallagan; Andi Sadarita; Genti Turnip; Nova Yulita Saragih; Muryani Surbakti (Sekolah Tinggi Teologi Baptis Medan, 2022)
School institutions must seek various ways to rebuild noble values in students as characters that they can be proud of. One of the efforts that schools can do to develop an education that is insightful in character building is to increase the role of schools in fostering the spiritual and personality of students. One of the subjects for faith building and personality formation is the subject of Christian Religious Education which teaches about love. With this in mind, in this study a research title was built which reads the relationship between Christian religious education and the development of Shiva's character. The methodology used is; type of correlational research. The application of the correlational research design is intended to test the hypothesis of the analysis of Christian religious education with the character development of students at SMK Pencawan Medan. The purpose of this study was to find out how the relationship between Christian religious education and student character development at SMK Pencawan Medan. This type of research data is interval data. Therefore, parametric statistics will be used. Parametric statistics were used to test the interval data hypotheses. The findings obtained from the implementation of Christian religious education are positively correlated with the character development of students at the population level. This means that there is a positive relationship between the implementation of Christian religious education with the character development of SMK Cawan Medan students, only the relationship is very low.Keywords: Christian education, character, growth AbstrakLembaga sekolah harus mengupayakan berbagai cara untuk membangun kembali nilai-nilai luhur dalam diri siswa sebagai karakter yang dibanggakan. Salah satu upaya yang dapat dilakukan oleh sekolah untuk mengembangkan pendidikan yang berspektif kepada pembentukan karakter adalah dengan cara meningkatkan peran sekolah dalam pembinaan spritual dan kepribadian siswa. Salah satu mata pelajaran untuk pembinaan iman dan pembentukan kepribadian tersebut adalah mata pelajaran Pendidikan Agama Kristen yang mengajarkan kasih. Dengan memperhatikan hal tersebut, maka dalam penelitian ini dibangun judul penelitian yang berbunyi Korelasi Pendidikan Agama Kristen dengan perkembangan Karakter siwa. Adapun Metodologi yang diapakai adalah; jenis penelitian korelasional. Penerapan desain penelitian korelasional dimaksudkan untuk menguji hipotesis analisis pendidikan agama Kristen dengan perkembangan karakter siswa di SMK Pencawan Medan. Tujuan Penelitian adalah untuk mengetahui Bagaimana Korelasi Pendidikan Agama Kristen dengan Perkembangan kareakter Siswa di SMK Pencawan Medan. Jenis data penelitian ini adalah data interval. Karena itu akan digunakan statistik parametris. Statistik parametris digunakan untuk menguji hipotesis data interval. Adapun temuan yang didapat pelaksanaan pendidikan agama Kristen berkorelasi positif dengan perkembangan karakter siswa di tingkat populasi . Artinya ada hubungan positif antara pelaksanaan pendidikan agama Kristen dengan perkembangan karakter siswa SMK pencawan medan, hanya hubungan itu sangat rendah.Kata Kunci: pendidikan agama kristen, karakter, perkembangan